Improving manual assembly lines devoted to complex electronic devices by applying Lean tools - Correia, Damásio (2020)
Manual assembly lines are usually deeply studied before implementation. Nevertheless, several problems upsurge when the product needs to be slightly changed. This is very common in complex electric and electronic devices usually produced in small batches, where the customers are demanding more and more features and the product needs to be continuously updated. However, these updates sometimes create huge difficulties for the previously installed assembly line, generating as well, line unbalancing and wastes of time regarding the initial situation. In this paper, a deep study of an adjusted assembly line of electronic devices was carried out using Value Stream Mapping (VSM) method to fully understand and document the different tasks and operations. The Lean Line Balancing (LLB) was also applied in order to reduce the line bottleneck by balancing the Task Time (TT) of each workstation so that there are no delays, and nobody is overburden with their task. Standardized processes and standardized work were also applied. During the line layout development stage, assembly fixtures, wastes reductions and visual management techniques were applied as well, different concepts were generated and, finally, the best solutions were selected. Throughout the study, many benefits for the studied manual assembly line were found, which can be considered as a strong motivation to apply Lean Manufacturing (LM) tools for better line efficiency and production rate.